IL CONCETTO DI STORIA LOCALE E L’INTERNATIONAL RESEARCH CENTER FOR LOCAL HISTORIES AND CULTURAL DIVERSITIES DELL’UNIVERSITÀ DEGLI STUDI DELL’INSUBRIA (Istituto Lombardo - Accademia di Scienze e Lettere • Rendiconti di Lettere, 2021)
I. Some remarks on the methodology of local history, and on some of its possible definitions, mainly focused on the important contribution given to the subject by Lewis Mumford’s essai The value of local history (1927). II. Since 1999, the International Research Center for Local Histories and Cultural Diversities of the University of Insubria has had, among its goals, research about and promotion of local histories and cultures. Interest in its own territorial area (Insubria region) is central, but it has also wider targets, including historiography theories. In its twenty years of activity, the Center has deepened historical research through advanced courses, publications, editions of historical sources, online databases and electronic resources, exhibitions, conferences and meetings, a library and a photographic archive. Multidisciplinary involvement, methodological issues, critical study of sources are the main features of its approach.